Forecasting Analysis of Raw Material Needs for Manjakani and Pepet Key in the Manufacture of Madurese Herb Products : Analisis Peramalan Kebutuhan Bahan Baku Manjakani dan Kunci Pepet pada Pembuatan Produk Jamu Madura - Asfan, Dian Farida; Ghooniyah, Indriana Mahrotul (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2024)
Demand for Madurese herbal products at PT. XYZ is increasing, especially for women's herbal medicine products, namely fragrant rapet herbal medicine. Uncertain demand means that the supply of raw materials for fragrant rapet herbal medicine, namely manjakani and pepet key, must be precise. Therefore, to meet the demand for herbal medicine, it is necessary to predict the need for raw materials for fragrant rapet herbal medicine. This article aims to predict the need for raw materials in the form of pepet and manjakani keys using various forecasting techniques, including average MA, WMA, ES and ES with trends. Forecasting results with the lowest MAD, MSE, and MAPE values—which show very minimal forecasting errors—will be selected for further examination. The results of the research show that for raw material needs for manjakani, the best forecast result value is 24.43 kg with the smallest percentage error value, namely MAPE of 11.255%, while for key raw material needs for pepet, the forecast result value is 13.59 kg with the smallest error percentage, namely MAPE of 14.851%.